Leadership Development by Contemplative Education: Learning Activities Development in a Course of Instructional Leadership and Curriculum Development - Thanaseelangkun, Chaturong (Ratchaphruek Journal, 2025)
The objective of this research was to develop instructional activities by applying participatory action research (PAR) processes within the classroom. The study focused on the characteristics, implementation process, outcomes, and students’ perceptions of contemplative education activities designed to develop leadership in the course Academic Leadership and Curriculum Development. The research was conducted over three cycles, involving purposively selected participants-three cohorts of thirty master’s degree students each, majoring in Educational Administration at Nakhon Ratchasima Rajabhat University. Research instruments included activity planning documents based on the Thai Qualifications Framework for Higher Education (TQF3), activity observation records, and a satisfaction interview form. The quality of the instruments was assessed through qualitative methods, and the data were analyzed using content analysis. The findings revealed that 1) The core principles of the activities emphasized self-awareness, interpersonal understanding, collaborative learning, experiential engagement, and pride in achievement. The activities integrated three essential components: mindfulness training, communication, and proactive participation, 2) The activity implementation process followed eight steps: (1) mindfulness and self-understanding, (2) dialogic learning through aesthetic conversation, (3) embracing diversity, (4) building trust, (5) collaborative engagement, (6) presenting a sense of pride, (7) fostering energy for relaxation, and (8) reflective friendship, 3) The outcomes indicated that students developed a deeper understanding of themselves, others, diversity, coexistence, co-creation, and the power of unity, and 4) Students expressed a high level of satisfaction with the activities. The contemplative education approach effectively supported experiential learning, promoting self-awareness, acceptance, and the ability to work harmoniously, effectively, and efficiently.